Enzymatic Hydrolysis of Broken Rice Protein: Antioxidant Activities by Chemical and Cellular Antioxidant Methods - Ren, Likun; Fan, Jing; Yang, Yang; Xu, Yue; Chen, Fenglian; Bian, Xin; Xing, Tonglin; Liu, Linlin; Yu, Dehui; Zhang, Na (Frontiers in Nutrition, 2021)
Excessive ROS is an important cause of aging, and supplementing antioxidants through diet is one of the important ways to delay aging. Some studies have confirmed that rice protease hydrolysate has antioxidant activity, but was rarely been investigated on cells. Thus, commercial enzymes alkaline enzyme, neutral enzyme, pepsin, chymotrypsin, and trypsin were selected to hydrolyze broken rice protein to obtained the corresponding hydrolysates, which were A-BRPH, N-BRPH, P-BRPH, C-BRPH, T-BRPH, respectively. Then the antioxidant properties of BRPHs were evaluated by different chemical and cellular antioxidation. Molecular weight, peptide length distribution and amino acid sequence were detected to insight into the antioxidant properties. Among BRPHs, the A-BRPH displayed the strongest hydroxyl radical scavenging activity (IC50=1.159 mg/mL) and metal ion-chelating activities (IC50=0.391 mg/mL). Furthermore, cellular antioxidation confirmed that A-BRPH significantly increased cell viability and inhibited the intracellular reactive oxygen species (ROS) release both in aging cells and cell-aging processes. SDS-PAGE results revealed that peptides with molecular weight less than 14.5 KDa were produced by enzymatic hydrolysis. Additionally, A-BRPH rich in low molecular weight (＜3 kDa) and short length peptides with some specific amino acids, like aromatic and hydrophobic amino acids, contribute to the antioxidant properties. This study provided theoretical to utilization of broken rice and confirmed that A-BRPH could be used in new anti-aging food and health products for human consumption.